2019
DOI: 10.1590/1519-6984.180184
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effect of Abamectin in the functional response of the predator Phytoseiulus persimilis (Athias-Henriot) on Tetranychus urticae (Koch) (Acari: Phytoseiidae, Tetranychidae)

Abstract: The biological control used for the control of Tetranychus urticae (Koch) is the predator mite Phytoseiulus persimilis (Athias-Henriot). It is important to the know the effects of acaricides on the biological behavior the Abamectin on the functional response of P. persimilis. The functional response of the predator was of type II exposed to concentration of Abamectin, the functional response parameters: successful attack rate (a'), handling time (Th), search efficiency and the maximum predation theory (T/Th) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A study of the Abamectin insecticide effect on Phytoseiulus confirmed the decrease in predatory activity of this acariphagus, with sub-lethal doses of the active substance up to 44,99% [13].…”
Section: Literature Reviewmentioning
confidence: 62%
“…A study of the Abamectin insecticide effect on Phytoseiulus confirmed the decrease in predatory activity of this acariphagus, with sub-lethal doses of the active substance up to 44,99% [13].…”
Section: Literature Reviewmentioning
confidence: 62%
“…Predation rate is potentially affected by sublethal concentrations of pesticides and ignoring this effect may lead to underestimating the negative effect of pesticides on the population of predators [12]. A few studies have evaluated the sublethal effect of pesticides on predation of treated phytoseiid mites [70], but to date, apart from our study [12], no data is available on the side effects of acaricides on prey consumption of subsequent generations of treated phytoseiid mites. For example, a study evaluated the effects of four selective pesticides on predation of treated females of a phytoseiid mite, Neoseiulus cucumeris.…”
Section: Side Effects Of Pesticides On Predation Of the Subsequent Ge...mentioning
confidence: 95%
“…In the other study, evaluation of the sublethal effect of abamectin on the functional response of P. persimilis, a significant decrease in attack rate and an increase in the handling time (Th) observed and indicating a negative effect of abamectin on the predation. Therefore, they reported that the predator requires more time to identify, persecute, consume, and digest the prey when it is under the influence of acaricide compared to control [70]. About it and as a result of predator biological behavior, Reddy (2013) mentions that the decrease in feeding is reflected by the exposure of thin layer residuals abamectin, when it enters in contact with the mite, it affects the capacity of the neurotransmitters GABA and glutamate stimulating the flow of chlorine ions into the nerve cells resulting in the loss of the function, these ions that flow inside the channel to an opening result in the loss of the cellular function and interruption of the nervous impulses and consequently, the mites stop their feeding, concluding a negative affect for the predatory mites [72].…”
Section: Side Effects Of Pesticides On Predation Of the Subsequent Ge...mentioning
confidence: 99%